A case report of gastric lymphocytic phlebitis, a rare mimic for malignancy. (2017) - Chan, Daniel L.; Ravindran, Praveen; Chua, Dorothy; Smith, Jason D.; Wong, King S.; Ghusn, Michael A.
Highlights: Gastric lymphocytic phlebitis is a rare benign venous inflammatory disease. This is the fourth case in the reported literature. Endoscopic and laparoscopic features are often a mimic for gastric malignancy. Given scarcity, surgical resection for histological confirmation is reasonable. Abstract: Introduction: Lymphocytic phlebitis is a benign condition characterised by inflammation of the veins and rarely affects the gastrointestinal tract. Reported cases present as acute abdomen and involve the colon or small intestine. We report the fourth case of gastric lymphocytic phlebitis in the literature. Presentation of case: A 74-year-old female presented with eight weeks of abdominal pain. Findings at endoscopy were suggestive of a malignant ulcer on the greater curvature of antrum, while biopsies showed chronic gastritis without malignancy. Appearance at diagnostic laparoscopy was consistent with a malignant gastric ulcer with serosal changes. Due to persistent pain and the macroscopic appearance, she proceeded to have an open subtotal gastrectomy and D2 lymph node clearance. Despite macroscopic appearance, the microscopic examination demonstrated no malignancy, and was consistent with lymphocytic phlebitis with overlying ulceration. Discussion: This case was a mimic for gastric malignancy, with the benign diagnosis only being made after surgical resection. Gastric lymphocytic phlebitis is a rare differential diagnosis for gastric ulcers when biopsies are negative, although preoperative diagnosis is difficult given the lesions do not involve the mucosa. Conclusion: If clinical history and endoscopic findings are suspicious for malignancy, despite normal biopsies, an aggressive surgical resection remains reasonable given the rarity gastric lymphocytic phlebitis.